2020
DOI: 10.1186/s12974-020-02006-w
|View full text |Cite
|
Sign up to set email alerts
|

The formyl peptide receptor agonist Ac2-26 alleviates neuroinflammation in a mouse model of pneumococcal meningitis

Abstract: Background Bacterial meningitis is still a cause of severe neurological disability. The brain is protected from penetrating pathogens by the blood-brain barrier and the innate immune system. The invading pathogens are recognized by pattern recognition receptors including the G-protein-coupled formyl peptide receptors (FPRs), which are expressed by immune cells of the central nervous system. FPRs show a broad spectrum of ligands, including pro- and anti-inflammatory ones. Here, we investigated t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 57 publications
0
8
0
Order By: Relevance
“…When binding to endogenous antiinflammatory/pro-resolving ligands (e.g., specialized proresolving lipid mediators lipoxin A4 and resolvin D1, and ANXA1) or pro-inflammatory ligands (e.g., formylated bacterial peptides and amyloid beta), FPR2/ALX receptor is activated and triggers downstream signaling cascades and subsequent distinct anti-or proinflammatory responses [50,51]. The immune regulation roles of ANXA1 and Ac2-26 through functional interaction with FPR2/ALX receptor have been reported using pharmacological and genetic approaches [36,[52][53][54]. In the current study, we utilized the specific FPR2/ ALX antagonist WRW4 and confirmed that Ac2-26 could bias the surface FPR2/ALX receptor of microglia/ macrophages to mediate phenotype polarization and inflammatory responses both in vivo and in vitro.…”
Section: Discussionmentioning
confidence: 99%
“…When binding to endogenous antiinflammatory/pro-resolving ligands (e.g., specialized proresolving lipid mediators lipoxin A4 and resolvin D1, and ANXA1) or pro-inflammatory ligands (e.g., formylated bacterial peptides and amyloid beta), FPR2/ALX receptor is activated and triggers downstream signaling cascades and subsequent distinct anti-or proinflammatory responses [50,51]. The immune regulation roles of ANXA1 and Ac2-26 through functional interaction with FPR2/ALX receptor have been reported using pharmacological and genetic approaches [36,[52][53][54]. In the current study, we utilized the specific FPR2/ ALX antagonist WRW4 and confirmed that Ac2-26 could bias the surface FPR2/ALX receptor of microglia/ macrophages to mediate phenotype polarization and inflammatory responses both in vivo and in vitro.…”
Section: Discussionmentioning
confidence: 99%
“…FPR deficiency is associated with increased bacterial burden and infiltration of the CNS by neutrophils and granulocytes, with distinct changes of the inflammatory immune reaction, resulting in higher mortality rates ( Oldekamp et al, 2014 ). Recent research has indicated that the anti-inflammatory effect also applies to meningitis ( Ruger et al, 2020 ). Another study using a mouse model of Streptococcus suis -induced meningitis, indicated that AnxA1 exerted anti-inflammatory effects via attenuating leukocyte infiltration, inflammatory mediator production, and astrocyte or microglial activation in the brain, along with decreasing neutrophil adherence to the endothelium through FPR2, thus inhibiting meningitis progression.…”
Section: Role Of Formyl Peptide Receptor In Neurological Disease Via Regulation Of Inflammationmentioning
confidence: 99%
“…To date, no studies have reported the involvement of these genes in the occurrence and development of CRSwNP. A recent study has confirmed that the formyl peptide receptor agonist Ac2-26 exerts an anti-inflammatory effect in a mouse model of bacterial meningitis through the formamide peptide receptor 2 ( FPR2 ) ( Rüger et al, 2020 ). FPR2 agonists could stimulate the resolution of inflammation by inhibiting neutrophil chemotaxis and stimulating macrophage phagocytosis, which may be the key to the treatment of chronic inflammatory diseases ( Asahina et al, 2020 ).…”
Section: Discussionmentioning
confidence: 97%